Approximation of homomorphisms and derivations of additive functional equation of n-Apollonius type in induced fuzzy Lie C*-Algebras - Ebadian, Ali; Aghalary, Rasoul; Abolfathi, Mohammad Ali (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
Using the fixed point method, we prove the generalized Hyers-Ulam stability of homomorphisms and derivations of additive functional equation of n-Apollonius type for afixed positive n with n>=2 on induced fuzzy C*-Algebras and induced fuzzy Lie C*-Algebras.